Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bbcan.2016.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic silencing of tumor suppressor genes: Paradigms, puzzles, and potential

Abstract: Cancer constitutes a set of diseases with heterogeneous molecular pathologies. However, there are a number of universal aberrations common to all cancers, one of these being the epigenetic silencing of tumor suppressor genes (TSGs). The silencing of TSGs is thought to be an early, driving event in the oncogenic process. With this in consideration, great efforts have been made to develop small molecules aimed at the restoration of TSGs in order to limit tumor cell proliferation and survival. However, the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 215 publications
4
116
0
6
Order By: Relevance
“…While the ultimate effects of many such mutations are not yet clear, their prominence indicates a central role for epigenomic dysregulation in oncogenesis [94, 98]. The most well established epigenetic changes are promoter hypermethylation and associated silencing of tumor suppressor genes [95, 99, 100] as well as genome-wide DNA hypomethylation [101103]. Hypomethylation of ERVs and L1s in many tumors has been documented [104106] and general transcriptional up-regulation of ERVs and L1s is often observed in cancers [33, 107109].…”
Section: Introductionmentioning
confidence: 99%
“…While the ultimate effects of many such mutations are not yet clear, their prominence indicates a central role for epigenomic dysregulation in oncogenesis [94, 98]. The most well established epigenetic changes are promoter hypermethylation and associated silencing of tumor suppressor genes [95, 99, 100] as well as genome-wide DNA hypomethylation [101103]. Hypomethylation of ERVs and L1s in many tumors has been documented [104106] and general transcriptional up-regulation of ERVs and L1s is often observed in cancers [33, 107109].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, epigenetic changes, especially the methylation of CpG islands in the promoters of tumor suppressor genes, may cause gene silencing and the onset of tumors [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…In metastatic breast cancer, endothelial growth factor receptor endocytosis was suppressed, leading to EZH2 overexpression through up-regulation of the MEK-ERK-Elk-1 pathway (21), with subsequent effects of the up-regulated EZH2 on cancer proliferation. EZH2 has also been shown to repress the expression of classic tumor suppressor genes such as CDKN2A and p53 (22) directly, and to reduce the levels of RAD51 leading to the activation of Raf1/ERK and β-catenin signalling (23). Several reports have revealed that EZH2 affects not only genetic but also epigenetic pathways.…”
Section: Discussionmentioning
confidence: 99%